Strengthening The Implementation of Recovery and Wellness Program: The Case of Meisic Police Station - Cabanayan, Maricris T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study evaluates the effectiveness of the Recovery and Wellness Program (RWP) in helping former drug users reintegrate into the community and in reducing crime within the area of Meisic Police Station, Manila. It presents the insights of program implementers, including police officers, social workers, and local government officials, as well as program graduates. Using a qualitative approach, data were gathered through semi-structured interviews with ten key participants and were analyzed thematically. Guided by the Transtheoretical Model of behavioral change, the research focused on five areas: program effectiveness, implementation strategies, prevention of relapse, challenges encountered, and proposed improvements. Findings indicate that the RWP has contributed to lowering crime rates and improving the lives of drug dependents. Nonetheless, its continued success depends on stronger community participation, sustained collaboration among agencies, and better logistical support.